Application of the structural-algorithmic analysis method for modeling work duty shift area control centers - Grishmanov, Dmytro; Pukhalska, Galina; Yarokhowytch, Olexander; Pysarchuk, Oleksii (НТУ "ХПІ", 2018)
Development and implementation new service ways in the air traffic services system are connected with the solution of complex tasks researching the features of familiar business models of duty shift and determination the direction of their development. The purpose of the articleis to analyze the existing business model of area control centers of air traffic controllers and search areas for their improvements. It is shown that insufficiently addressed issues relating to the problems of interaction between the air traffic controllers among themselves and with automation tools. In this regard, the harmonization of the business models is needed in order to research, process information and training tasks, that takes into consideration the requirements of visibility and accessibility, while maintaining the possibility of analytical and experimental studies. To improve the business model of the area control center duty shift has been proposed to add other elements into the situation detection scheme and classify the initiating situations. The article shows that it is rational to complement existing methods of modeling activities of air traffic controllers by structurally-algorithmic analysis method and method of generalized network models activity in order to address the research, information and training tasks.

Розробка і впровадження в систему обслуговування повітряного руху нових способів обслуговування пов'язані з вирішенням комплексу завдань з дослідження особливостей відомих моделей діяльності чергової зміни, визначення напрямів їх вдосконалення. Метою статтіє проведення аналізу існуючих моделей діяльності авіаційних диспетчерів районних диспетчерських центрів і пошук напрямків щодо їх вдосконалення. Показано, що недостатньо повно вирішені питання, що стосуються проблем взаємодії диспетчерів між собою та з засобами автоматизації. У зв'язку з цим необхідна уніфікація моделей діяльності з метою вирішення дослідницьких, інформаційних та тренажних завдань, що передбачає врахування вимог наочності та доступності при збереженні можливості проведення аналітичних і експериментальних досліджень. Для вдосконалення моделей діяльності чергової зміни районного диспетчерського центру пропонується внести додаткові елементи в схему розпізнавання ситуації і класифікувати ініціюючі ситуації. У статті показано, що для комплексного вирішення дослідницьких, інформаційних та тренажних завдань раціональним є доповнення існуючої методики моделювання діяльності авіаційних диспетчерів методом структурно-алгоритмічного аналізу та методом узагальнених мережевих моделей діяльності.
Застосування методу структурно-алгоритмічного аналізу для побудови моделей роботи чергової зміни районного диспетчерського центру
Keywords: air traffic controller; duty shift; business model; network models; авіаційний диспетчер; модель діяльності; мережеві моделі